Предельные теоремы для одномерных краевых задач - Кодлюк, Т.И.; Михайлец, В.А.; Рева, Н.В. (Український математичний журнал, 2013)
Дослiджується границя за параметром у рiвномiрнiй нормi розв’язкiв загальних крайових задач для систем лiнiйних звичайних диференцiальних рiвнянь першого порядку. Отримано узагальнення теореми I. Т. Кiгурадзе (1987) щодо таких задач. Воно максимально послаблює умови на асимптотичну поведiнку коефiцiєнтiв систем. Крiм того, знайдено достатнi умови рiвномiрної збiжностi матриць Грiна до матрицi Грiна граничної крайової задачi. We study the limit with respect to a parameter in the uniform norm for the solutions of general boundary-value problems for systems of linear ordinary differential equations of the first order. A generalization of the Kiguradze theorem (1987) to this class of problems is obtained. The conditions imposed on the asymptotic behavior of the coefficients of systems are weakened as much as possible. Sufficient conditions for the uniform convergence of Green matrices to the Green matrix of the limit boundary-value problem are also established.